Metabolic changes in Brycon cephalus (Teleostei, Characidae) during post-feeding and fasting - Figueiredo-Garutti, M. L.; Navarro, I; Capilla, E.; Souza, RHS; Moraes, G.; Gutierrez, J.; Vicentini-Paulino, MLM (Elsevier B.V., 2002)
Metabolic changes during the transition from post-feeding to fasting were studied in Brycon cephalus, an omnivorous teleost from the Amazon Basin in Brazil. Body weight and somatic indices (liver and digestive tract), glycogen and glucose content in liver and muscle, as well as plasma glucose, free fatty acids (FFA), insulin and glucagon levels of B. cephalus, were measured at 0, 12, 24, 48, 72, 120, 168 and 336 h after the last feeding. At time 0 h (the moment of food administration, 09.00 h) plasma levels of insulin and glucagon were already high, and relatively high values were maintained until 24 h post-feeding. Glycemia was 6.42 +/- 0.82 mM immediately after food ingestion and 7.53 +/- 1.12 MM at 12 h. Simultaneously, a postprandial replenishment of liver and muscle glycogen reserves was observed. Subsequently, a sharp decrease of plasma insulin occurred, from 7.19 +/- 0.83 ng/ml at 24 h of fasting to 5.27 +/- 0.58 ng/ml at 48 h. This decrease coincided with the drop in liver glucose and liver glycogen, which reached the lowest value at 72 h of fasting (328.56 +/- 192.13 and 70.33 +/- 14.13 mumol/g, respectively). Liver glucose increased after 120 h and reached a peak 168 h post-feeding, which suggests that hepatic gluconeogenesis is occurring. Plasma FFA levels were low after 120 and 168 h and increased again at 336 h of fasting. During the transition from post-feeding to fast condition in B. cephalus, the balance between circulating insulin and glucagon quickly adjust its metabolism to the ingestion or deprivation of food. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: post-feeding; starvation; glycemia; FFA; insulin; glucagon; hepatic and muscle glycogen; hepatic and muscle glucose; fish; Brycon cephalus